Beneath the Copper—Pediatric Wilson's Disease Cirrhosis and Hepatocellular Carcinoma: A Case Report with Literature Review - Rosencrantz, Richard A.; LeCompte, Lesli; Yusuf, Yasmin (Seminars in Liver Disease, 2015)
Primary hepatic malignancies are uncommon in pediatrics. Tumors such as hepatocellular carcinoma (HCC) develop typically in the setting of chronic liver disease. The incidence of HCC in Wilson's disease-related cirrhosis is disproportionately lower than in many other forms of end-stage liver disease. A preadolescent girl presented with Wilson's disease cirrhosis and a HCC requiring orthotopic liver transplantation. This case highlights the need to consider hepatic malignancies even in young Wilson's disease patients. Pediatric Wilson's disease and the hepatic tumor literature are reviewed.
Keywords: Wilson's disease; hepatocellular carcinoma; pediatrics; liver transplantation